Luďa Klusáková – Laure Teulières (eds.): Frontiers and Identities. Cities in Regions and Nations.: Edizioni Plus – Pisa University Press, Pisa 2008, 346 s. - Illner, Michal (Lidé města, 2009)
A review of the book by Luďa Klusáková and Laure Teulières.